Exploring Synergies at the Interface of the Amyloid and Signaling Fields - Jafari, Naeimeh (My University, 2020)
The fields of amyloid and signaling have traditionally developed through largely separate routes. However, several intersections and synergies exist between these two research areas. For example, kinase catalyzed phosphorylation is known to affect self-association in several amyloidogenic proteins. Here, we explore further instances for how methods and concepts originally pioneered in one field may benefit the other. We show how allosteric conformational transitions at the basis of signaling regulation can also serve as a basis to design sensors for binding of ligands to amyloid inhibitory chaperones. Conversely, we also illustrate how signaling benefits from the amyloid field. For example, we show that amyloid formation may serve as a non-classical mechanism for protein kinase A (PKA) activation. This is in contrast to the classical mechanism for PKA activation, which relies on cAMP-dependent conformational changes of the regulatory subunits. However, the classical cAMP-dependent activation of PKA alone may not suffice to rationalize the phenotype of enhanced PKA activation observed for known disease related mutations in the regulatory subunits of PKA, such as the Carney Complex (CNC), which is a generalized tumor predisposition. Several CNC mutants exhibit reduced affinity for cAMP, which appears incompatible with the overactivation of PKA in the context of a PKA regulation that is dependent on cAMP alone. The activation of PKA by CNC mutation-induced polymerization of inhibitory regulatory subunits and consequent amyloid formation offers a simple but effective solution to solve this apparent paradox and explain CNC phenotypes. Overall, this dissertation highlights several reciprocally beneficial opportunities at the interface between amyloids and signalling.